Pengaruh Laju Pengeringan Terhadap Perubahan Fisiologi BENIH Avicennia marina (Forsk.) Vierh. - Halimursyadah Halimursyadah (Jurnal Agrista, 2008)
The Effect of Drying Rate on Physiological Changes in Seed of Avicennia marina (Forsk.) Vierh.ABSTRACT. Avicennia marina seed has been classified a highly recalcitrant that need the right handling for maintaining seed viability. The objective og this study was to investigate physiological, biochemical, anatomical changes at various drying rate, fast, medium and slow drying. Seed moisture content, germination percentage, speed of germination, index of vigor, time to reach 50% germination, electrolyte leachates, oligosaccharide content were determined, and anatomical of embryonic axes was observed at various times durng desiccation. The result of the experiment show that the moisture content of A. marina seed was 60.75-64.67% at shedding. Time to reach the lowest moisture content (32-33%) at fast, medium and slow drying were 6, 10 and 14 days, respectively. First and final count in germination test were 13 and 22 days. Critical moisture content of seed based on time to reach 50% viability (P50) were 37.25, 43.28, and 45.92% for fast, medium and slow drying, respectively. The critical moisture content based on speed of germination were 36.51, 42.47, and 45.01% for fast, medium and slow drying, respectively.